Induced debonding method for composite material bonding assembly based on expandable graphite
By using an adhesive with thermoplastic coating and expandable graphite particles in composite bonding structures, controllable debonding of bonded components is achieved, solving the problem of scrapping of bonded structures due to defects and damage, increasing the reuse value of components, and promoting the sustainable application of composite materials.
Patent Information
- Application Number
- CN202510768996.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-09-26
AI Technical Summary
Existing technologies have failed to effectively solve the problem of scrapped parts due to defects in the manufacturing process of composite bonded structures and the problem of disposal after damage in service, resulting in high economic burden and impact on delivery cycle.
Thermoplastic coating@expandable graphite particles are prepared using a shell-core structure preparation method. By dispersing and coating them in an adhesive, the volume expansion of the thermoplastic coating@expandable graphite is utilized to generate cracks in the adhesive structure, thereby achieving debonding between adhesive components and avoiding structural scrapping.
Controllable debonding of composite bonded structures is achieved, maintaining internal quality and performance intact, reducing the risk of structural scrapping during manufacturing and service, increasing the reuse value of components, and promoting the sustainable application of composite materials.
Smart Images

Figure CN120699555A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sustainable application of composite materials, and particularly relates to an induced debonding method for composite material adhesive components based on expandable graphite. Background Art
[0002] Adhesive bonding is widely used in the assembly and connection of composite structures, such as the stringer-skin reinforcements in fuselages and wings. However, during the manufacturing process, adhesively bonded structures can easily experience defects such as debonding in the bonded areas due to poor structural adhesive film quality or deviations in curing process parameters. In severe cases, these defects can lead to structural failure. Furthermore, accidental impacts during service, such as bird strikes, hail, and lightning strikes, can cause varying degrees of impact damage to adhesively bonded structures, compromising their integrity and seriously impacting their service safety.
[0003] Currently, conventional methods for composite material manufacturing involve controlling process parameters such as temperature, pressure, and vacuum to suppress internal defects in composite structures. Alternatively, particles such as carbon nanotubes and graphene can be added between composite layers to enhance the impact resistance of the structure. However, existing technologies primarily focus on preventing manufacturing defects and protecting against impact damage, failing to fundamentally address the inherent challenges of manufacturing defects and post-service damage in composite bonded structures. When manufacturing defects exceed the out-of-tolerance delivery limits set by technical specifications, or structural damage exceeds the scope of manual repairs and is difficult to repair using traditional methods, the impact of structural scrapping on manufacturing / repair costs and lead times is unavoidable. Given the high material and manufacturing costs of load-bearing composite structures in aviation, scrapping or replacing damaged structures can be a significant financial burden. Therefore, reducing the risk of structural scrapping caused by manufacturing defects and innovating methods for the disposal of damaged bonded structures, effectively debonding bonded components to restore their reusability, is a highly effective approach to achieving sustainable composite material development and a key to the sustainable application of composite aerospace structures and green, low-carbon development. Summary of the Invention
[0004] In response to the shortcomings of the existing technology, the present invention provides a method for induced debonding of composite material adhesive components based on expandable graphite. On the one hand, it is suitable for avoiding the problem of part scrapping caused by defects in the adhesive surface during the manufacturing process of composite material adhesive structures. On the other hand, it can solve the problem of disposing of components whose internal quality and performance remain intact among parts damaged in service in composite material adhesive structures.
[0005] A method for inducing debonding of a composite adhesive assembly based on expandable graphite, comprising the following steps:
[0006] (1) A shell-core structure preparation method is adopted, wherein a thermoplastic resin is dissolved in a solvent, and then expandable graphite is uniformly dispersed in the mixed solution, and then filtered and separated to obtain thermoplastic coating@expandable graphite particles;
[0007] (2) subjecting the thermoplastic coating@expandable graphite particles obtained in step (1) to surface treatment, filtering and drying, and then mechanically grinding to obtain coupled thermoplastic coating@expandable graphite particles;
[0008] The ambient temperature during the preparation process is equal to or greater than the initial expansion temperature of the expandable graphite;
[0009] (3) dispersing the coupled thermoplastic coating@expandable graphite particles of different particle sizes in the adhesive, pre-preparing the adhesive layer or directly applying it to the bonding surface, and then combining it with the bonding component to complete the bonding and curing;
[0010] (4) When defects or damage occur locally in the adhesive structure and the components need to be disassembled, the adhesive structure is heated to generate cracks inside the adhesive layer through the volume expansion of the thermoplastic coating @ expandable graphite, and the cracks propagate to cause the adhesive layer to crack, thereby achieving debonding between the adhesive components.
[0011] in:
[0012] In the step (1), the shell-core structure preparation method is one of an emulsion suspension method and a solution mixing method.
[0013] In the step (1), the thermoplastic resin is selected from one of polyetheretherketone, polyetherimide and polyarylethersulfoneketone, has a heat deformation temperature of ≥150°C, and the mass fraction of the thermoplastic resin in the solvent is 1% to 10%.
[0014] In the step (1), the boiling point of the solvent is lower than the initial expansion temperature of the expandable graphite. When the thermoplastic resin is polyetheretherketone, the solvent is concentrated sulfuric acid, and the mass fraction of the concentrated sulfuric acid is ≥98%; when the thermoplastic resin is polyetherimide, the solvent is N,N-dimethylformamide; when the thermoplastic resin is polyarylethersulfoneketone, the solvent is N,N-dimethylacetamide.
[0015] In the step (1), the expandable graphite is expandable graphite with a low starting temperature, an initial expansion temperature of 160° C., a particle size of 32 mesh to 80 mesh, and a mass fraction of the expandable graphite in the mixed solution of 0.5% to 5%. When concentrated sulfuric acid is used as the solvent, deionized water is added for dilution, and then ammonia water with a mass fraction of 20% to 40% is added for neutralization.
[0016] In the step (2), the surface treatment specifically comprises: dispersing the thermoplastic coating@expandable graphite particles in a coupling agent or a surfactant, and achieving good dispersion of the thermoplastic coating@expandable graphite particles by ultrasonic oscillation or mechanical stirring;
[0017] The mass fraction of the thermoplastic coating@expandable graphite particles in the surfactant is 0.1 wt.% to 2.0 wt.%.
[0018] In the step (3), the adhesive is an epoxy resin adhesive or a bismaleimide resin adhesive, which is similar to or the same as the resin matrix of the bonding component, has a curing temperature lower than the initial expansion temperature of the expandable graphite, and a glass transition temperature not lower than the glass transition temperature of the cured resin of the bonding component.
[0019] In the step (3), the mass fraction of the coupled thermoplastic coating@expandable graphite particles in the adhesive is 0.1% to 2.0%.
[0020] In the step (3), the adhesive is applied by spraying or scraping, and the adhesive layer containing the thermoplastic coating and expandable graphite is obtained in one step or layer by layer, and the overall thickness of the adhesive layer is 0.1 mm to 1.0 mm.
[0021] In step (3), after adding the thermoplastic coating @ expandable graphite particles, the impact toughness of the adhesive is ≥1.17J / cm 2 , single lap tensile shear strength ≥5.50MPa.
[0022] In the step (4), the temperature of the heating treatment is not lower than the initial expansion temperature of the expandable graphite and is not higher than the curing temperature or post-curing temperature of the adhesive assembly.
[0023] In the step (4), the heating treatment time depends on the actual heating treatment temperature, with the influence on the mechanical properties of the adhesive assembly being ≯10% as the benchmark.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention uses thermoplastic coating and expandable graphite to synergistically improve the bonding performance of composite materials, giving components an induced debonding function and broadening the application field of expandable graphite.
[0026] 2. The method of the present invention is particularly suitable for bonding thermosetting composite materials with long-term service temperatures exceeding 150°C. It utilizes the micro-nano effect of the thermoplastic coating and expandable graphite particles to synergistically improve the impact toughness and bonding strength of the adhesive.
[0027] 3. The present invention avoids the influence of excessive expansion temperature on the performance of the components in the adhesive structure by optimizing the expansion time and temperature design, and does not cause obvious thermal damage to the main structure on the basis of achieving induced debonding between adhesive components.
[0028] 4. This invention achieves controllable induced debonding of components by regulating the particle size distribution of the thermoplastic coating and expandable graphite in the adhesive layer, reconstructing defective or damaged adhesive structures while preserving the internal quality and performance of the components for reuse, thus forming a new method for the sustainable application of composite materials.
[0029] 5. The present invention can avoid the problem of expensive structural scrapping due to factors such as adhesive surface defects and impact damage during the manufacturing and use of composite materials. By leveraging the reuse value of disassembled components, energy conservation, efficiency improvement and emission reduction in the field of composite material manufacturing and maintenance can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 In Example 1 of the present invention, a comparison chart of the mode I fracture toughness of the adhesive before and after adding the prepared polyetheretherketone@expandable graphite to the adhesive;
[0031] Figure 2 In Example 1 of the present invention, a comparison chart of the single-layer tensile shear strength of the adhesive before and after adding the prepared polyetheretherketone@expandable graphite to the adhesive;
[0032] Figure 3 Phase contrast images of the adhesive layer in the composite material adhesive structure before and after temperature-induced expansion in Example 1 of the present invention; wherein (a) is before temperature-induced expansion, and (b) is after temperature-induced expansion;
[0033] In the figure: 1-bonded component A, 2-bonded component B, 3-adhesive layer (containing 1% mass fraction of polyetheretherketone @ expandable graphite), 4-expansion and cracking of the adhesive layer on the side adjacent to the bonded component A, 5-expansion and cracking of the adhesive layer on the side adjacent to the bonded component B, 6-expansion and cracking inside the adhesive layer. DETAILED DESCRIPTION
[0034] The contents disclosed in the present invention include the preparation method of thermoplastic coating @ expandable graphite, the use of thermoplastic coating @ expandable graphite to toughen adhesives, the doping of thermoplastic coating @ expandable graphite to improve the bonding strength of adhesives, the combination of thermoplastic coating types and expandable graphite particle sizes, the debonding of components in adhesive structures based on temperature-induced expansion of expandable graphite, and the control of expansion path and debonding degree by regulating the particle size distribution of thermoplastic coating @ expandable graphite in the adhesive layer. These key technical points should all be considered as the scope of protection of the present invention.
[0035] The present invention will be further described below with reference to specific implementation cases, but the present invention is not limited to these embodiments.
[0036] The materials selected in the embodiment of the present invention are: the thermoplastic coating is a high-performance polyetheretherketone resin, the expandable graphite is an expandable graphite with a low starting temperature, an initial expansion temperature of 160°C, and a particle size of 32 mesh and 80 mesh; the adhesive component is Composite material (curing temperature 177℃, long-term service temperature 185℃), the adhesive layer matrix is epoxy resin adhesive Henkel Loctite EA9390 AERO (curing temperature 94℃, long-term service temperature 177℃).
[0037] In the embodiment of the present invention, the mass fraction of the concentrated sulfuric acid used is 98%, and the mass fraction of the ammonia water used is 20%.
[0038] Example 1
[0039] A method for inducing debonding of a composite adhesive assembly based on expandable graphite, comprising the following steps:
[0040] (1) 2 g of polyetheretherketone (PEEK) was dissolved in 100 mL of concentrated sulfuric acid at 22 ± 4 °C to prepare a PEEK sulfuric acid solution. Subsequently, 1 g of expandable graphite with a particle size of 32 mesh was added and stirred for 30 min to prepare a mixed solution. 200 mL of deionized water was slowly added to form an emulsion. 100 mL of ammonia water was then added to neutralize the sulfuric acid in the emulsion. Polyetheretherketone@expandable graphite particles were obtained by multiple washing and filtration.
[0041] (2) The polyetheretherketone@expandable graphite particles obtained in step (1) are dispersed in a 2 wt.% silane coupling agent / ethanol solution by mechanical stirring, filtered and dried, and then mechanically ground to prepare coupled polyetheretherketone@expandable graphite with a particle core particle size of 32 mesh. The above operation is repeated to prepare coupled polyetheretherketone@expandable graphite particles with a particle core particle size of 80 mesh.
[0042] (3) The 0.25 mm thick adhesive layer is discretized into three adhesive layer units in the thickness direction, which respectively contain coupled polyetheretherketone@expandable graphite with expandable graphite particle sizes of 32 mesh, 80 mesh and 32 mesh, and the adhesive layer thicknesses are 0.06 mm, 0.13 mm and 0.06 mm, respectively. Specifically, polyetheretherketone@expandable graphite with different particle sizes is dispersed in EA9390 adhesive, and the mass fraction of coupled thermoplastic coating@expandable graphite particles in the adhesive is 0.5%. After heating to 55 °C, the adhesive layer unit thickness is controlled by adjusting the spraying parameters using adhesive spraying technology, and the polyetheretherketone@expandable graphite particle size gradient distribution adhesive layer is constructed layer by layer on the surface of the cured adhesive component A, forming a dense-sparse-dense gradient distribution state of polyetheretherketone@expandable graphite in the adhesive layer, and then combined with the cured adhesive component B to complete bonding at 94 °C / 220 min.
[0043] The obtained composite material adhesive components were disassembled and verified: the adhesive structure was heated at 180°C for 30 minutes. The 80-mesh expandable graphite in the middle adhesive layer unit was efficiently expanded to complete the cracking of the adhesive layer to achieve debonding between the adhesive components. At the same time, with the help of the detailed expansion of the 32-mesh expandable graphite in the surface adhesive layer units of the adjacent adhesive components A and B, the workload of surface polishing and other tasks before re-bonding of subsequent adhesive components (A and / or B) was reduced.
[0044] The adhesive used in this embodiment has an impact toughness of 0.86 J / cm before being doped with polyetheretherketone@expandable graphite particles. 2 The single lap shear strength is 2.14MPa. The comparison of the adhesive's type I fracture toughness before and after adding the prepared polyetheretherketone @ expandable graphite is shown in the figure below. Figure 1 As shown in the figure, the comparison of the single tensile shear strength of the adhesive is as follows Figure 2 As shown, the impact toughness of the adhesive layer doped with 1wt.% polyetheretherketone@expandable graphite particles is 1.17J / cm 2 The single lap shear strength is 5.51MPa. After doping, the impact toughness is increased by 36.04%, and the single lap tensile shear strength is increased by 157.5%.
[0045] The metallographic changes in the composite material interface structure before and after temperature-induced expansion are shown in the figure. Figure 3 As shown in the figure, the bending strength of the original adhesive assembly is 815.28 MPa. After being treated at 180℃ for 30 minutes, the bending strength of the adhesive assembly after separation is 768.45 MPa, with a decrease of only 5.74%.
Claims
1. A method for inducing debonding of composite adhesive components based on expandable graphite, characterized in that: The specific steps include: (1) A shell-core structure preparation method is adopted, wherein a thermoplastic resin is dissolved in a solvent, and then expandable graphite is uniformly dispersed in the mixed solution, and then filtered and separated to obtain thermoplastic coating@expandable graphite particles; (2) subjecting the thermoplastic coating@expandable graphite particles obtained in step (1) to surface treatment, filtering and drying, and then mechanically grinding to obtain coupled thermoplastic coating@expandable graphite particles; The ambient temperature during the preparation process is equal to or greater than the initial expansion temperature of the expandable graphite; (3) dispersing the coupled thermoplastic coating@expandable graphite particles of different particle sizes in the adhesive, pre-preparing the adhesive layer or directly applying it to the bonding surface, and then combining it with the bonding component to complete the bonding and curing; (4) When defects or damage occur locally in the adhesive structure and the components need to be disassembled, the adhesive structure is heated to generate cracks inside the adhesive layer through the volume expansion of the thermoplastic coating @ expandable graphite, and the cracks propagate to cause the adhesive layer to crack, thereby achieving debonding between the adhesive components.
2. The method for inducing debonding of a composite material adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (1), the shell-core structure preparation method is one of an emulsion suspension method and a solution mixing method.
3. The method for inducing debonding of a composite material adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (1), the thermoplastic resin is selected from one of polyetheretherketone, polyetherimide and polyarylethersulfoneketone, has a heat deformation temperature of ≥150°C, and the mass fraction of the thermoplastic resin in the solvent is 1% to 10%.
4. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (1), the boiling point of the solvent is lower than the initial expansion temperature of the expandable graphite. When the thermoplastic resin is polyetheretherketone, the solvent is concentrated sulfuric acid, and the mass fraction of the concentrated sulfuric acid is ≥98%; when the thermoplastic resin is polyetherimide, the solvent is N,N-dimethylformamide; when the thermoplastic resin is polyarylethersulfoneketone, the solvent is N,N-dimethylacetamide.
5. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (1), the expandable graphite is expandable graphite with a low starting temperature, an initial expansion temperature of 160° C., a particle size of 32 mesh to 80 mesh, and a mass fraction of the expandable graphite in the mixed solution of 0.5% to 5%.
6. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 5, characterized in that: When concentrated sulfuric acid is used as the solvent, deionized water must be added for dilution, and then 20% to 40% ammonia water must be added for neutralization.
7. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (2), the surface treatment specifically comprises: dispersing the thermoplastic coating@expandable graphite particles in a coupling agent or a surfactant, and achieving good dispersion of the thermoplastic coating@expandable graphite particles by ultrasonic oscillation or mechanical stirring; The mass fraction of the thermoplastic coating@expandable graphite particles in the surfactant is 0.1 wt.% to 2.0 wt.%.
8. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (3), the adhesive is an epoxy resin adhesive or a bismaleimide resin adhesive, which is similar to or the same as the resin matrix of the bonding component, has a curing temperature lower than the initial expansion temperature of the expandable graphite, and a glass transition temperature not lower than the glass transition temperature of the cured resin of the bonding component; the mass fraction of the coupled thermoplastic coating@expandable graphite particles in the adhesive is 0.1% to 2.0%; The adhesive is applied by spraying or scraping, and an adhesive layer containing thermoplastic coating and expandable graphite is obtained by coating once or layer by layer. The overall thickness of the adhesive layer is 0.1 mm to 1.0 mm.
9. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 1, characterized in that: In step (3), after adding the thermoplastic coating @ expandable graphite particles, the impact toughness of the adhesive is ≥1.17J / cm 2 , single lap tensile shear strength ≥5.50MPa.
10. The method for inducing debonding of a composite adhesive assembly based on expandable graphite according to claim 1, characterized in that: In the step (4), the temperature of the heating treatment is not lower than the initial expansion temperature of the expandable graphite and is not higher than the curing temperature or post-curing temperature of the adhesive assembly; the time of the heating treatment depends on the actual heating treatment temperature, with the influence on the mechanical properties of the adhesive assembly being ≯10% as the benchmark.